2005
DOI: 10.1634/stemcells.2004-0183
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of Bone Marrow–Derived Fibroblasts Recruited into Fibrotic Lesions

Abstract: Fibroblasts, which are widely distributed and play a key part in tissue fibrosis, are phenotypically and functionally heterogeneous. Recent studies reported that bone marrow can be a source of tissue fibroblast. In the study reported here, we investigated in vivo characterization of bone marrowderived fibroblasts recruited into various fibrotic lesions. Mice were engrafted with bone marrow isolated from transgenic mice expressing green fluorescent protein (GFP), and fibrotic lesions were induced by cancer impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
123
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 44 publications
2
123
1
4
Order By: Relevance
“…Although the fibroblasts of the host tissue are the most obvious source of the newly formed tumor-associated stroma, recruitment of mesenchymal precursors from bone marrow cannot be excluded. 69,70 It is also probable that transforming growth factor beta 1 (TGFb1) plays a major role in the differentiation of resting fibroblasts to myofibroblasts. 71,72 Cancer cells produce large amounts of TGFb1, especially at the invading tumor front where they interact with fibroblasts of the host organ.…”
Section: Possible Mechanisms Of Fibroblast Activationmentioning
confidence: 99%
“…Although the fibroblasts of the host tissue are the most obvious source of the newly formed tumor-associated stroma, recruitment of mesenchymal precursors from bone marrow cannot be excluded. 69,70 It is also probable that transforming growth factor beta 1 (TGFb1) plays a major role in the differentiation of resting fibroblasts to myofibroblasts. 71,72 Cancer cells produce large amounts of TGFb1, especially at the invading tumor front where they interact with fibroblasts of the host organ.…”
Section: Possible Mechanisms Of Fibroblast Activationmentioning
confidence: 99%
“…These data provide unique insight into how skin grafts facilitate tissue repair and identify strategies germane to regenerative medicine for skin and, perhaps, other ectodermal defects or diseases. In skin, studies have shown that BM provides fibroblast-like cells in the dermis (of hematopoietic and mesenchymal lineages) and that the number of these cells increases after skin wounding (3,4). BM can also generate epithelial cells, i.e., keratinocytes, in the epithelia, although the precise derivations and mechanisms to raise BM-derived keratinocytes are not fully known (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…A caracterização fenotípica das células antes da diferenciação é fundamental para informar sobre o grau de pureza da cultura, pois a medula óssea pode apresentar CTM, células hematopoéticas (2,29) e fibroblastos (30). As células hematopoéticas expressam, entre outras moléculas, CD45 (2,31) que também pode ser expressa em fibroblastos (30).…”
Section: Discussionunclassified
“…As células hematopoéticas expressam, entre outras moléculas, CD45 (2,31) que também pode ser expressa em fibroblastos (30). A molécula CD73 pode ser expressa tanto em fibroblastos (2) quanto em CTM (30).…”
Section: Discussionunclassified
See 1 more Smart Citation